Study on the type and density of marine debris at Lhok Bubon Beach, West Aceh - Samsul Bahri; Hayatun Nufus; Heriansyah Heriansyah; Faliqul Isbah (Program Studi Akuakultur, Fakultas Pertanian, Universitas Almuslim, 2025)
Marine debris poses a serious threat to both marine ecosystems and human health. With its extensive coastline and numerous islands, Indonesia is especially vulnerable to pollution from marine waste. The waters of Aceh, including Lhok Bubon tourist beach, are becoming increasingly polluted by plastic debris due to local coastal activities and poor waste management practices. This study classifies marine debris and analyzes its composition at Kuala Bubon tourist beach in Samatiga District, West Aceh Regency. Data collection took place in July 2023 at two Stations: one close to traders and crowds, and another in a more remote area. At Station I, hard plastic waste dominated, comprising 30,73% of total waste, while at Station II, it accounted for 53,32%. The density of marine debris was 77,45 items/m² at Station I and 110,65 items/m² at Station II. Waste weight density was 2207,5 grams/m² and 2137,5 grams/m², respectively. Hard and soft plastics were the most common waste types. Hard plastic made up 56,55% of total waste at Station I, whereas soft plastic reached 89,52% at Station II. The study reveals a high concentration of plastic waste, particularly in less-maintained areas, emphasizing the need for better waste management practice.